Analisis Penerapan Audit Syariah dalam Menjaga Kepatuhan Syariah pada Bank Syariah di Indonesia - Jessica Valentina Darwis; Kholisna Auliyana Zulfa; Meiysa Umadi Putri; Fikri Rizki Utama (Ekopedia: Jurnal Ilmiah Ekonomi, 2026)
This study discusses the implementation of sharia audits in maintaining sharia compliance in Islamic banks in Indonesia. The study uses a qualitative descriptive approach through literature review methods to understand the role of sharia audits in supervising operational activities and ensuring compliance with Islamic principles in Islamic banking institutions. Data were collected from scientific journals, books, official reports, and previous studies related to sharia audits and Islamic banking. The results of the study indicate that sharia audits have an important role in maintaining sharia compliance through supervision of banking products, operational activities, financing systems, and implementation of contracts in accordance with Islamic principles. Sharia audits also help management identify violations, minimize the risk of non-compliance, and maintain public trust in Islamic banking institutions. In addition, the role of the Sharia Supervisory Board and internal audit strengthens the implementation of supervision in Islamic banks. However, this study also found several obstacles in implementing sharia audits, including limited human resources who understand sharia auditing, differences in interpretation of sharia principles, technological developments, and the increasing complexity of banking products. Therefore, strengthening the sharia audit system and improving auditor competence are important steps in supporting the effectiveness of sharia compliance supervision in Islamic banks.